2018
DOI: 10.1186/s13613-018-0395-5
|View full text |Cite
|
Sign up to set email alerts
|

Biological scoring system for early prediction of acute bowel ischemia after cardiac surgery: the PALM score

Abstract: BackgroundBowel ischemia is a life-threatening emergency defined as an inadequate vascular perfusion leading to bowel inflammation resulting from impaired colonic/small bowel blood supply. Main issue for physicians regarding bowel ischemia diagnosis lies in the absence of informative and specific clinical or biological signs leading to delayed management, resulting in a poorer prognosis, especially after cardiac surgery. The aim of the present series was to propose a simple scoring system based on biological d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…Bowel ischemia is a life-threatening condition with a mortality rate of more than 40%. 30 A retrospective study by Eris and colleagues 31 concluded that the condition appears to be more frequent in patients undergoing isolated CABG, reporting a mean postoperative onset at 1 to 30 days. However, it can also occur a few hours after cardiac surgery, leading to a more ominous prognosis compared to a later onset.…”
Section: Ischemic Bowelmentioning
confidence: 99%
See 1 more Smart Citation
“…Bowel ischemia is a life-threatening condition with a mortality rate of more than 40%. 30 A retrospective study by Eris and colleagues 31 concluded that the condition appears to be more frequent in patients undergoing isolated CABG, reporting a mean postoperative onset at 1 to 30 days. However, it can also occur a few hours after cardiac surgery, leading to a more ominous prognosis compared to a later onset.…”
Section: Ischemic Bowelmentioning
confidence: 99%
“…Further investigation showed that a procalcitonin level of more than 0.57 ng·mL −1 requires surgical resection due to intractable gut ischemia. The PALM score devised by Zogheib and colleagues, 30 based on serum procalcitonin, lactate, aspartate aminotransferase, and myoglobin levels, allows early diagnosis of bowel ischemia after cardiac surgery, with a high degree of accuracy. Lactate is produced by anaerobic glycolysis that occurs due to decreased perfusion, whereas procalcitonin secretion is increased in ischemia due to the production of interleukin-6 and tumor necrosis factor-α.…”
Section: Liver Failurementioning
confidence: 99%
“…[ 10 , 11 ] The Youden index was used to determine the cut-off value calculated as max (sensitivity + specificity - 1). [ 12 ] A p value of <0.05 was considered statistically significant.…”
Section: Methodsmentioning
confidence: 99%
“…The estimated incidence of AMI was reportedly 1–3% after cardiovascular surgery (CS) [ 5 8 ]. Several factors, such as advanced age, hypertension, heart failure, prolonged ventilation, use of norepinephrine, and elevated serum levels of procalcitonin, myoglobin, lactate, and aspartate aminotransferase (AST), are reported to be risk factors for AMI after CS [ 9 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the mortality risk formula was modified to establish a P-POSSUM score that can predict a mortality rate more accurately [ 15 ]. The mortality rate in cases of AMI after CS was reportedly 52.9–81.3% [ 7 , 9 ]. However, a few studies have evaluated predictors of clinical outcomes of patients after surgery for AMI following CS.…”
Section: Introductionmentioning
confidence: 99%